ANALISIS RASIO LIKUIDITAS UNTUK MENILAI KINERJA KEUANGAN PT. JASA RAHARJA - L. Tobing, Vargo Christian; Simatupang, Eva Malina (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the development of the liquidity ratio of PT Jasa as a measuring tool in assessing the company's financial performance. The liquidity ratios analyzed include Current Ratio, Cash Ratio, and Cash Turn Over. This research uses a quantitative approach, using secondary data with a documentation study approach in the form of a financial position report and income statement of PT Jasa Raharja. The results of the analysis show that the company's Current Ratio and Cash Turn Over are consistently above industry standards, which reflects the company's ability to meet short-term obligations and effectiveness in managing operational cash. However, the company's Cash Ratio is still below industry standards, which indicates limited cash to immediately pay off current debt. Thus, the overall liquidity performance of PT Jasa Raharja is in a fairly good condition, but the company needs to improve cash management to strengthen short-term financial resilience.